Gambaran Penggunaan Sistem Informasi Kesehatan Elektronik di Puskesmas Kalideres - Elsa Safitri; Yurita Mailintina; Ria Efkelin (Universitas Malahayati Lampung, 2024)
ABSTRACT The importance of information systems in processing data into information that can be used by decision makers, especially in the field of health services. In the era of revolution 4.0, Indonesia sees an opportunity to strengthen its position in global competition in various sectors, including health services. Therefore, the government is expected to be able to respond to various issues and situations that arise by utilizing information systems effectively. Quantitative descriptive research with cross-sectional design. This quantitative research aims to look at human behavior in a social phenomenon that can be measured and is objective. This research uses valid and reliable instruments, as well as appropriate and accurate statistical analysis to produce data that matches the actual situation. The majority of respondents felt good regarding the reliability of the electronic health information system at the Kalideres Health Center, with 98% of respondents feeling good, all respondents felt good regarding the flexibility of the health information system at the Kalideres Health Center, and all respondents felt good regarding the integration of the health information system at the Kalideres Health Center. Thus, it can be concluded that users of the electronic health information system (SIKDA Optima) at the kalideres health center are rated well by respondents based on aspects of reliability, flexibility and system integration. Keywords: System Usage, Electronic Health Information System, Service, Health Center ABSTRAK Pentingnya sistem informasi dalam mengolah data menjadi informasi yang dapat digunakan oleh pengambil keputusan, terutama dalam bidang pelayanan kesehatan. Dalam era revolusi 4.0, indonesia melihat kesempatan untuk memperkuat posisinya dalam persaingan global di berbagai sektor, termasuk pelayanan kesehatan. Oleh karena itu, pemerintah di harapkan mampu menanggapi berbagai isu dan situasi yang muncul dengan memanfaatkan sistem informasi secara efektif. Penelitian deskriptif kuantitatif dengan desai cross-sectional. Penelitian kuantitatif ini bertujuan untuk melihat tingkah laku manusia secara fenomena sosial yang dapat diukur dan bersifat objektif. Penelitian ini menggunakan instrumen yang valid dan dapat diandalkan, serta analisis statistik yang sesuai dan akurat untuk menghasilkan data yang sesuai dengan situasi aktual. Mayoritas responden merasa baik terkait dengan reliabilitas sistem informasi kesehatan elektronik di puskesmas kalideres, dengan 98% responden merasa baik, seluruh responden merasa baik terkait dengan fleksibilitas sistem informasi kesehatan di puskesmas kalideres, dan seluruh responden merasa baik terkait dengan integrasi sistem informasi kesehatan di puskesmas kalideres. Dengan demikian, dapat disimpulkan bahwa pengguna sistem informasi kesehatan elektronik (SIKDA Optima) di puskesmas kalideres dinilai baik oleh responden berdasarkan aspek reliabilitas, fleksibilitas dan integrasi sistem. Kata Kunci: Penggunaan Sistem, Sistem Informasi Kesehatan Elektronik, Pelayanan, Puskesmas